The role of iron and haemochromatosis gene mutations in the progression of liver disease in chronic hepatitis C. Issue 2 (1st February 2002) - Thorburn, D; Curry, G; Spooner, R; Spence, E; Oien, K; Halls, D; Fox, R; McCruden, E A B; MacSween, R N M; Mills, P R
Abstract : Background: Chronic hepatitis C virus (HCV) infection is frequently associated with elevated markers of iron stores. Recessively inherited mutations in the HFE gene are responsible for iron accumulation in most cases of hereditary haemochromatosis and may have a role in HCV infection. They may also be associated with progressive liver fibrosis although this remains controversial. Aims: To assess the prevalence of HFE mutations in Scottish HCV infected patients and to explore the effect of the carrier state on serum and liver iron stores, and the severity of liver disease. Patients: A total of 164 patients with antibodies to HCV who underwent liver biopsy were assessed prospectively. Methods: Each patient was screened for HFE mutations (Cys282Tyr and His63Asp). Iron markers were assessed in serum (ferritin, transferrin saturation) and on liver biopsy (stainable iron, liver iron concentration (LIC) and hepatic iron index). Results: There were 67 (41%, 26 Cys282Tyr, 33 His63Asp, eight compound) heterozygotes. Forty four (28%) patients had elevated serum iron markers, 24 (15%) had stainable liver iron, and five (3%) had elevated LICs. Carriage of HFE mutations was not associated with any clinical, biochemical, virological, or pathological features, including accumulation of liver iron. Elevated serum iron markers were associated with male sex, increased alcohol consumption, and increased liver inflammation and fibrosis. Patients with elevated LICs were older, acquired HCV infection earlier, and had more liver inflammation. Conclusions: Patients with chronic HCV infection frequently have elevated serum iron markers although elevated LICs are uncommon. Elevated serum iron studies and LICs occur in patients with more severe liver disease. Carriage of HFE mutations, although frequently observed in these HCV infected patients, does not have a role in the accumulation of iron or the progression of liver disease in HCV infection.